Knowledge and Perception Regarding Hypertension among Hypertensive Patients at a Tertiary Hospital in Kathmandu, Nepal - Bashyal, Sabita Pandey; Thapa, Narbada (Journal of Advanced Academic Research, 2020)
Background: Hypertension has a great impact on cardiovascular disease and death all over the world. Low and middle-income countries including Nepal are facing higher disease burden because of complications arise from uncontrolled hypertension. Patient’s knowledge and perception play an important role for the proper management of hypertension. There are limited studies related to knowledge and perception of hypertension, therefore, this study aimed to assess the knowledge and perception of hypertension among hypertensive patients at a tertiary hospital in Nepal.Methods: This is a hospital based, mixed-method, cross-sectional study which was conducted among 400 hypertensive patients in the outpatient department of Sahid Gangalal National Heart Center, Kathmandu, Nepal. Patients who were diagnosed as hypertensive at least 6 months before were selected by simple random sampling technique and were interviewed using semi- structured questionnaire, and interview schedule from March to May 2019. Data were analyzed using descriptive and inferential statistics.   Results: The mean age of the respondents was 58.86 ±11.07 years and nearly half (47.8%) of them were in the age group of 60 years and above. More than half, (58%) were male, 77.8% were overweight, about half of them had a significant family history of hypertension with first degree relatives. Regarding the knowledge, the total mean score was 16.16±3.032 and had significant difference with age (p= 0.002), gender (p=.000), education (p=0.002), occupation (p=0.000), and duration of HTN diagnosis (p=0.000). Majority of them perceived hypertension as less serious illness and had significant difference with education level (p=0.001) and duration of HTN diagnosis (p=0.000).Conclusions: Majority of participants had inadequate knowledge of hypertension and they perceived hypertension as less severe illness which might hinder the adherence to treatment recommendations. Hence, mass awareness program strategies might be helpful to increase hypertension related knowledge and perception.